Exploring Pedagogical Approaches in the Implementation of the Independent Curriculum: A Case Study from Baubau, Indonesia - Sardiana Sardiana; Hamsinah Tahir; Laode Supardi (AL-ISHLAH: Jurnal Pendidikan, 2025)
The Independent Curriculum introduced in Indonesia aims to provide greater flexibility for teachers and students by promoting student-centered, contextual, and competency-based learning. However, its successful implementation depends significantly on teacher readiness and instructional strategies. This study explores the pedagogical approaches used by Economics teachers in implementing the Independent Curriculum at a senior high school in Baubau, Indonesia. A qualitative case study approach was employed, involving one Economics teacher, the principal, a curriculum supervisor, and 26 tenth-grade students. Data were collected through interviews, classroom observations, documentation, and questionnaires. Analysis followed Miles and Huberman’s interactive model, involving data reduction, display, and conclusion drawing, supported by triangulation for validity. Findings reveal that the teacher implemented several strategies aligned with curriculum goals, including participation in In-House Training (IHT), development of learning modules (ATP, TP, ACP), and the use of multimedia and project-based instruction to support student engagement. Assessment strategies ranged from authentic and portfolio-based assessments to traditional exams. Students responded positively to the flexibility of the curriculum, though challenges such as limited teacher experience and time management were noted. The study concludes that while pedagogical implementation shows promise, further support in the form of training, collaboration, and structured guidance is essential for optimizing curriculum outcomes. These findings underscore the importance of institutional support in scaling curriculum reform.